Pengembangan Media Puzzle Interaktif untuk Pengenalan Huruf pada Anak Usia 5-6 Tahun di Taman Kanak-Kanak - Inrafa, Shaumy Darojatun; Kurnia, Reni; Yusri, Meldi Ade Kurnia; Masnur, Alkadri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to develop interactive puzzle-based learning media that is specifically designed to introduce letters to early childhood in Kindergarten Negeri Madani. Conventional learning media are considered less interactive in the letter recognition process, while visual- and play-based approaches have proven to be more effective for children. This research is a type of Research and Development (R&D) research with a 4-D development model (four-D model). This model consists of 4 stages of development including Define, Design, Develop, Disseminate. This media was developed systematically and tested for validity and practicality using a questionnaire. The results of the validity test reached 87.17% for the material aspect and 86.11% for the media aspect, while the practicality test achieved an average score of 81.25%. This interactive puzzle media is proven to be able to increase children's interest in learning letters with a fun approach and support their motor and cognitive development